Challenges faced by family businesses in India and strategies/measures to overcome them. - Singh, Harmandeep (2011)
ABSTRACT In this research, we study the problems (weaknesses) and challenges that family-run enterprises face and suggest the strategies and measures that should be enforced in order to ensure that these enterprises continue to be successful in the long run. A majority of the businesses in India are family-run businesses. Miller and Rice (1967) state, that family involvement differentiates these businesses from other business. However, is different always good? Well, yes and no. In this study, we evaluate the negative side, i.e. the problems, weaknesses, and challenges that family-run enterprises face. We comprehend, review, and analyse literature related to family businesses with the main focus on the problems and challenges that an Indian family-run business faces. This research work also suggests the strategies and measures that should be enforced in order to ensure that these enterprises continue to be successful in the long run; the research focuses only on Indian family-run businesses. The reason for the selection of Indian family-run businesses is that in India, a majority of the businesses ranging from small to big multi-million-dollar companies are family-run businesses, and hence, the Indian economy is considerably dependent on these firms. This dependence emphasises the need for these enterprises to prosper in future and hence needs to be understood and analysed.